Rise Of The AIUDF: Analysing Its Emergence And Political Impact In Assam (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper aims to provide a comprehensive analysis of the emergence and role of the All-India United Democratic Front (AIUDF) in the politics of Assam. The paper explores the historical background of the party, its ideology, electoral performance, and the impact it has on the socio-political landscape of the state. By examining various factors, including regional identity politics, minority representation, and electoral alliances, this paper seeks to shed light on the AIUDF's significance in shaping the political dynamics of Assam.